The "Knyagynya" tract as a center for the preservation of the phytological identity of the Eastern Podillia - Mudrak, O. V.; Berezovska, R. L.; Mudrak, G. V. (Man and Environment. Issues of Neoecology, 2023)
Purpose. To describe the phytodiversity of the "Knyaginya" Tract - a complex natural monument of national importance. Methods. Field, cartographic, analytical, descriptive, comparative, expeditionary, bioindicative, statistical, systemic, biomonitoring. Results. The diversity of phytocenoses of the "Knyaginya" Tract - a complex natural monument of national importance with an area of 53 hectares, located within the boundaries of the Pischanska settlement territorial community of the Tulchyn district of the Vinnytsia region - was established. The importance of the object of the nature reserve fund for the formation of the regional econetwork of Eastern Podillia was clarified. The species richness of various phytocenoses of the relatively small area of the studied object is substantiated. 527 species of higher vascular plants were identified, of which 440 are autochthonous and 87 are adventitious, which is 43.5% of the total phytodiversity of Eastern Podillia, which includes 1210 species. In terms of the number of species, the studied area is one of the most valuable reference areas of the region’s plant gene pool. Conclusions. In order to preserve the rare phytodiversity of Eastern Podillia, it is proposed to expand the boundaries of the complex natural monument "Knyaginya" Tract.